Review of Timothy D. Taylor. 2007. Beyond Exoticism: Western Music and the World. Durham, NC, and London: Duke University Press - Zuberi, Nabeel (Current Musicology, 2007)
This book reminds us how the creation, sound and consumption of music-as well as the ways in which we produce located knowledge about music- are shaped by power relations with long histories. The regimes through which “the West” dominates, represents, and incorporates its “Others” lie at at the heart of Timothy D. Taylor’s intellectual project. Taylor is a professor of ethnomusicology and musicology; positioned within and between two disciplinary formations, Beyond Exoticism is the follow-up to the excellent Strange Sounds (2001), which focused on the role of technology in the construction of musical imaginaries since World War II. Taylor deftly combines lucidity and nuance in a work of such breadth. Beyond Exoticism is crisply written, mercifully free of jargon and addresses important concepts and issues in a vocabulary that graduates, undergraduates, and non-academic readers should be able to understand and apply in their own encounters with music of many kinds.